2015
DOI: 10.1002/aur.1508
|View full text |Cite
|
Sign up to set email alerts
|

Can Neurotypical Individuals Read Autistic Facial Expressions? Atypical Production of Emotional Facial Expressions in Autism Spectrum Disorders

Abstract: The difficulties encountered by individuals with autism spectrum disorder (ASD) when interacting with neurotypical (NT, i.e. nonautistic) individuals are usually attributed to failure to recognize the emotions and mental states of their NT interaction partner. It is also possible, however, that at least some of the difficulty is due to a failure of NT individuals to read the mental and emotional states of ASD interaction partners. Previous research has frequently observed deficits of typical facial emotion rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
182
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 175 publications
(194 citation statements)
references
References 38 publications
10
182
1
1
Order By: Relevance
“…Increased variability in autistic actions may mean that a given autistic participant's action models are a poorer fit to those of other autistic individuals (note that autistic facial expressions have also been shown to have more idiosyncratic qualities, which may similarly impair expression understanding; Brewer et al, 2016;Macdonald et al, 1989). Alternatively, autistic action models may be tuned to both atypical (autistic) and typical movements.…”
Section: Discussionmentioning
confidence: 99%
“…Increased variability in autistic actions may mean that a given autistic participant's action models are a poorer fit to those of other autistic individuals (note that autistic facial expressions have also been shown to have more idiosyncratic qualities, which may similarly impair expression understanding; Brewer et al, 2016;Macdonald et al, 1989). Alternatively, autistic action models may be tuned to both atypical (autistic) and typical movements.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first accounts of the characteristics presented by children with ASD (Asperger 1944;Kanner 1968), uncommon emotional facial expression's production has been described (Brewer et al 2016;Faso et al 2015;Volker et al 2009). …”
Section: Emotional Response Incoherence In Asdmentioning
confidence: 99%
“…The few studies that have examined alexithymia in children with ASD have found that, similarly to adults (Berthoz and Hill 2005), alexithymia is more prevalent among children with ASD than among TD children (Griffin et al 2015;Rieffe et al 2007). In one study it was found that the facial expressions of individuals with higher levels of alexithymia appeared to be odder than of those with lower levels (Brewer et al 2016). Which led the authors to suggest that despite the overlap between alexithymia and ASD, alexithymia may be linked to atypical emotional expressions in ASD (Brewer et al 2016).…”
Section: Emotional Response Incoherence In Asd and The Role Of Alexitmentioning
confidence: 99%
See 2 more Smart Citations